2000
DOI: 10.1177/1066480700084008
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Birthing Trends: Impact on Couples and Families

Abstract: Current treatments for infertility often involve medical interventions that offer promising and sometimes unexpected results. One consequence has been a burgeoning of multifetal conceptions throughout the world. The purpose of this article is to review research on the effects of the multiple-birth experience on couples and families. Needs for future research and implications for couple and family counselors are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
0
26
0
1
Order By: Relevance
“…Akerman (1997) in a study of parents of triplets found that fathers were closely and competently involved in infant care and felt emotionally close to their babies. Fathers who are closely involved in daily infant care from birth report greater enjoyment and satisfaction than those who are not (Weigel et al, 2000). This involvement may not be sustained.…”
Section: Twin Research December 2003mentioning
confidence: 93%
See 4 more Smart Citations
“…Akerman (1997) in a study of parents of triplets found that fathers were closely and competently involved in infant care and felt emotionally close to their babies. Fathers who are closely involved in daily infant care from birth report greater enjoyment and satisfaction than those who are not (Weigel et al, 2000). This involvement may not be sustained.…”
Section: Twin Research December 2003mentioning
confidence: 93%
“…Stillbirth or neonatal death of one of a multiple precipitates the complex coincidence of death and detachment from one infant with the formation of attachment to another. Prematurity or infant disability also involves grief for the loss of an imagined child and the gradual adjustment to the real infant (Klock, 2001;Weigel et al, 2000). Thorpe et al (1991) found that the most distressed mothers of twin 5-year-olds were those with a prolonged and inexpressible sadness associated with losing one twin when the other was living.…”
Section: Twin Research December 2003mentioning
confidence: 99%
See 3 more Smart Citations